Evaluation of phylogenetic relationships in Lemnaceae using nuclear ribosomal data. (18th June 2014) - Tippery, N. P.; Les, D. H.; Crawford, D. J.
Abstract: Nuclear DNA sequence data are essential for obtaining a complete understanding of plant species relationships, yet these data have been conspicuously absent from phylogenetic analyses of Lemnaceae (duckweeds). Using a modified Sanger sequencing protocol, we obtained DNA sequences of duckweed nuclear ribosomal regions, including 18S and 26S rDNA genes, the external transcribed spacer (ETS) and the frequently used internal transcribed spacer (ITS). After obtaining sequence data for all Lemnaceae species, we ascertained that prior difficulty in sequencing the ITS regions likely resulted from extremely rigid secondary structures, precipitated by a high proportion of G/C nucleotides. In phylogenetic analyses, nuclear ribosomal data largely supported relationships that had been inferred using chloroplast DNA sequence data.